Knowledge mapping and management - White, Don 1957- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2002)
This book presents information on knowledge management and mapping in the context of the learning organization, including the design of information technology in Internet-enabled organization forms
A collection of 30 papers written by White and an international group of scholars. - Includes bibliographical references and index. - Title from PDF t.p. (viewed on May 28, 2010)
Keywords: Knowledge management; Organizational learning